Odpowiedź :
Odpowiedź:
d)
x⁶ + 4x³ - 32 = 0
za x³ wstawiam a
a² + 4a -32 = 0
Δ = 4² - 4 * 1 *(- 32) = 16 + 128 = 144
√Δ = √144 = 12
a₁ = ( - 4 - 12)/2 = - 16/2 = - 8
a₂ = ( -4+ 12)/2 = 8/2 = 4
x³ = - 8 ∨ x³ = 4
x = ∛(- 8) ∨ x = ∛4
x = - 2 ∨ x = ∛4
f)
x⁸ - 4x⁴ - 24 = 0
Za x⁴ wstawiam a
a² - 4a - 24 = 0
Δ = ( - 4)² - 4 * 1 * (- 24) = 16 + 96 = 112
√Δ = √112 = √(16 *7) = 4√7
a₁ = (4 - 4√7)/2 = 2(2 - 2√7)/2 = 2 - 2√7
a₂ = (4 + 4√7)/2 = 2(2 + 2√7)/2 = 2 + 2√7
x⁴ = 2 - 2√7 ∨ x⁴ = 2 + 2√7
x = ⁴√(2 - 2√7) ∨ x = ⁴√(2 + 2√7)
Ponieważ 2 - 2√7 jest liczbą mniejsza od 0 , więc x = ⁴√(2 + 2√7)